Does the Level of Temporal Demand Affect Activation of the Mental Timeline? - Katharina Kühne; Alex Miklashevsky; Anastasia Malyshevskaya (Journal of Cognition)
The space-time congruency effect indicates faster processing of past-/future-related words with the left/right response key, suggesting the presence of the horizontal Mental Time Line (MTL). Typically, this effect is observed in the tasks with high temporal demand (i.e., past versus future categorization), but not in those with the low relevance of the time dimension (i.e., sensicality judgments). However, it remains unclear whether intermediate levels of temporal demand are sufficient to activate the MTL. To address this, we conducted three experiments in which participants categorized the same set of temporal words based on their relation to living entities (Experiment 1), space (Experiment 2), and general time (Experiment 3). In individual analyses of the experiments, the space-time congruency effect was absent in Experiment 1. In Experiment 2, the effect emerged in reaction times but not in accuracy. In Experiment 3, it was observed in both measures. Subsequent comparisons across experiments suggested reliable differences between Experiments 2 and 3 in reaction times and between Experiment 3 and the other two experiments in accuracy. Our results provide evidence that MTL activation depends on the level of temporal demand required by the task. The findings support the notion that mental representations are context-sensitive rather than fixed.